RQA and TTW Strategies: Which Can Increase the Students’ Concepts Understanding? - Sagala, Rumadani; Sari, Putri Mardiana; Firdaos, Rijal; Amalia, Ricadesta (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
Concepts understanding is the key for students to have quality knowledge. A good concepts understanding will affect the achievement of other abilities such as the ability to think critically and creatively. This study aims to see the application of two strategies, namely RQA (Reading-Questioning-Answering) and TTW (Think-Talk-Write) in improving students' concepts understanding. The research method used is posttest only control group design with a total sample of 60 students divided into two experimental classes. The treatment for the first experimental class was the RQA strategy while the treatment for the second experimental class was the TTW strategy. After the treatments, the students were given 20 questions about concepts understanding motion and force material. Based on the results of testing and data analysis, it is found that there are differences in the achievement of students' conceptual understanding between RQA strategy and TTW strategy. Based on the results of the study, it can be concluded that the three steps in the TTW strategy have a better impact on the seven aspects of conceptual understanding compared to the RQA strategy. This study provides recommendation for teachers to correctly choose learning strategies according to the character of the material to be taught.